A surface active coupled flame retardant additive and its preparation method and application
By using surfactant coupled flame retardant additives in flame retardant conveyor materials for coal mines, the problem of degradation of mechanical properties caused by the addition of flame retardant is solved, and the mechanical properties and flame retardant properties of the material are significantly improved.
Patent Information
- Application Number
- CN202411114618.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-14
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2044-08-14
AI Technical Summary
The existing flame retardant conveyor belt materials used for underground coal mines have the problem of degradation of mechanical properties due to the addition of flame retardant, and neoprene materials have the disadvantages of easy crystallization, poor processing performance, unstable performance, difficult storage, and high cost.
The surfactant coupled flame retardant additive is used. By comprehensively designing the surfactant and silane coupling agent groups, the additive promotes the compatibility and dispersion between rubber polymer materials and other components, improves the production process, improves the physical and mechanical mechanical properties of the material, and catalyzes the material to become carbon when burned, thereby improving the flame retardant performance.
It significantly improves the mechanical properties and flame retardant performance of flame retardant conveyor belt materials used in coal mines, solves the problem of mechanical properties degradation caused by the addition of flame retardant, and reduces the cost of the material.
Smart Images

Figure CN118955553B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of flame-retardant conveyor belt additives for underground coal mines, and more specifically, to an additive with surface active coupled flame retardant effect, and a preparation method and application thereof. Background Art
[0002] Coal is the main support of my country's energy structure. In order to improve the transportation efficiency of coal, people usually use mechanical equipment for transportation, such as conveyors. The main component of the conveyor is the conveyor belt composed of covering rubber, rubber core layer and skeleton material.
[0003] Although conveyors can effectively improve the efficiency of coal transportation, as the conveyor capacity, transportation distance and load increase, the tensile stress on the conveyor belt increases significantly. At the same time, due to the irregular shape, heavy weight and sharp surface of minerals, minerals can easily cause serious damage and wear to the conveyor belt. Even if the conveyor belt rubs and produces sparks during transportation, it can easily lead to fire, resulting in significant loss of life and property. In response to this, the state requires coal mine conveyor belts to have flame retardant properties and meet the requirements of MT / T668.
[0004] At present, most flame-retardant conveyor belts used in coal mines are made of chloroprene rubber, and fillers such as flame retardants are added to improve their flame retardancy. However, chloroprene rubber has the disadvantages of easy crystallization, poor processing performance, unstable performance, difficult storage, and high cost. At the same time, the addition of a large amount of powder flame retardant will lead to a decrease in the mechanical properties of the conveyor belt. Therefore, there is an urgent need for a material with both excellent flame retardant and mechanical properties for use in coal conveyor belts. Summary of the invention
[0005] In order to improve the disadvantage that the addition of conventional flame retardants will lead to a decrease in the mechanical properties of conveyor belts, the present application provides an auxiliary agent with surface active coupled flame retardant effect and a preparation method and application thereof.
[0006] In the first aspect, the present application provides a surface active coupled flame retardant additive, which adopts the following technical solution:
[0007] A surface active coupled flame retardant additive, the molecular structure of which is: .
[0008] The surface active coupled flame retardant additive in the present application can promote the compatibility between rubber polymer materials and reinforcing agents, activators, antioxidants, accelerators, flame retardant fillers and vulcanizers, and promote the mutual dispersion, mixing and coupling between different components, thereby improving the production process and improving the physical and mechanical properties of the material; catalyze and promote carbonization during material combustion, thereby improving the flame retardant properties of the material.
[0009] The surface active coupled flame retardant additive in the present application integrates the surfactant group and the silane coupling agent group into the same molecule, so that the surface active coupled flame retardant additive has the chemical properties of both the surfactant and the silane coupling agent, forming a new structure of the surface active coupled flame retardant additive molecule.
[0010] The surface active coupled flame retardant additive in this application mainly has three functions: (a) containing siloxane groups and hydroxyl groups, it plays the role of silane coupling agent. (b) containing hydrophobic alkyl groups, sodium sulfonate groups, carboxyl groups and quaternary ammonium salt groups, it plays the role of surfactant, dispersant and surface modifier. (c) containing sodium sulfonate groups, it plays the role of catalyst, promotes the catalytic carbonization of materials when they are thermally decomposed, and improves the thermal stability and flame retardant properties of the materials; and contains flame retardant element silicon in the molecule, which has flame retardant effect.
[0011] The surface active coupled flame retardant additive in the present application contains a long-chain hydrophobic alkyl group, a hydroxyl group, a carboxyl group, a sodium sulfonate group, a siloxane group and a quaternary ammonium salt group, so that its performance is better.
[0012] In the second aspect, the present application provides a method for preparing a surface active coupled flame retardant additive, using the following technical solution:
[0013] A method for preparing a surface active coupled flame retardant additive comprises the following steps:
[0014] S1. Add octadecylamine and isopropanol into a reactor, and then add 3-glycidyloxypropyltrimethoxysilane, and mix and react to obtain an intermediate. The structural formula of the intermediate M is: ;
[0015] S2. Add acrylic acid to the intermediate M, mix and react to obtain the intermediate N, the structural formula of the intermediate N is: ;
[0016] S3. Adding an aqueous solution of sodium 3-chloro-2-hydroxypropyl sulfonate to the intermediate N, mixing and reacting, to obtain a surface active coupled flame retardant additive.
[0017] The preparation method of the surface-active silane coupling agent of the present application does not pollute the environment.
[0018] Preferably, the reaction equations of each step of the preparation method of the surface-active silane coupling agent are:
[0019] S1: ;
[0020] S2: ;
[0021] S3: .
[0022] Preferably, the molar ratio of octadecylamine, 3-glycidyloxypropyltrimethoxysilane, acrylic acid and sodium 3-chloro-2-hydroxypropylsulfonate is 1:(1.0-1.2):(1.0-1.2):(1.0-1.3).
[0023] Preferably, the mass ratio of octadecylamine to isopropanol is 1:(1.5-3.5).
[0024] Preferably, the mass fraction of sodium 3-chloro-2-hydroxypropyl sulfonate in the sodium 3-chloro-2-hydroxypropyl sulfonate aqueous solution is 27%-39%.
[0025] Preferably, in S1, the reaction temperature is 65-80°C and the reaction time is 3-5h.
[0026] Preferably, in S2, the reaction temperature is 65-80°C and the reaction time is 2-4h.
[0027] Preferably, in S3, the reaction temperature is 65-80°C and the reaction time is 4-6h.
[0028] Preferably, the method for preparing the surface active coupled flame retardant additive comprises the following steps:
[0029] S1. Add octadecylamine and isopropanol into a reactor, then add 3-glycidyloxypropyltrimethoxysilane, and mix and react at a temperature of 65-80° C. for 3-5 hours to obtain an intermediate. The structural formula of the intermediate M is: ;
[0030] S2. Add acrylic acid to the intermediate M, mix and react at a temperature of 65-80° C. for 2-4 hours to obtain the intermediate N. The structural formula of the intermediate N is: ;
[0031] S3. Add the aqueous solution of sodium 3-chloro-2-hydroxypropyl sulfonate to the intermediate N, mix and react at a temperature of 65-80° C. for 4-6 hours to obtain a surface active coupled flame retardant additive.
[0032] In a third aspect, the present application provides an application of a surface active coupled flame retardant additive, using the following technical solution:
[0033] The invention discloses an application of a surface active coupled flame retardant auxiliary agent, wherein the surface active coupled flame retardant auxiliary agent is used for improving the flame retardant properties and mechanical properties of a rubber flame retardant material for a flame retardant conveyor belt used underground in a coal mine.
[0034] Preferably, the flame retardant rubber material for flame retardant conveyor belts used underground in coal mines includes the following raw materials in parts by mass: 40-60 parts of natural rubber, 40-60 parts of butadiene rubber, 40-50 parts of reinforcing agent, 4-6 parts of activating agent, 0-3 parts of stearic acid, 4-6 parts of aromatic oil, 1.5-3.5 parts of antioxidant, 0.8-2.8 parts of accelerator, 20-30 parts of chlorinated paraffin, 2-6 parts of antimony trioxide, 10-20 parts of aluminum hydroxide, 0.1-0.75 parts of a surface active coupled flame retardant additive and 1-4 parts of a vulcanizing agent.
[0035] Aromatic oil has good rubber compatibility, can improve the processing performance of rubber, and promote the mixing and dispersion of fillers in rubber. After adding additives with surface active coupling flame retardant effect, the dispersion and coupling between organic and inorganic components in the flame retardant rubber material for flame retardant conveyor belts used in coal mines are significantly improved, thus showing better mechanical properties and flame retardant properties.
[0036] Antimony trioxide and aluminum hydroxide are both inorganic flame retardants with excellent flame retardant effects. Among them, the flame retardant mechanism of antimony trioxide mainly includes three aspects: gas phase flame retardant, solid phase flame retardant and chemical reaction flame retardant. Specifically, antimony trioxide can release antimony pentoxide at high temperature, and antimony pentoxide can react with free radicals in the fuel to inhibit the combustion. At the same time, antimony trioxide can also form a dense isolation layer at high temperature, thereby hindering combustion and heat conduction and slowing down the spread of flames. In addition, antimony trioxide can also react chemically with free radicals and active substances in the flame propagation chain reaction, thereby blocking the chain reaction and achieving a flame retardant effect.
[0037] The flame retardant mechanism of aluminum hydroxide mainly includes three aspects: dehydration, dilution and isolation. Specifically, at high temperature, aluminum hydroxide can decompose water, thereby absorbing heat, reducing the surface temperature of the fuel, and inhibiting the formation and spread of flames. At the same time, the generation of water vapor will also dilute the oxygen concentration, thereby inhibiting the formation and spread of flames. In addition, aluminum hydroxide can form an aluminum oxide isolation layer when burning, thereby hindering combustion and heat conduction, and slowing down the spread of flames. When antimony trioxide is used in combination with aluminum hydroxide, antimony trioxide and aluminum hydroxide will synergistically flame retard in different aspects to obtain a better flame retardant effect.
[0038] Preferably, the antimony trioxide and aluminum hydroxide are doped into the organic-inorganic hybrid material cage-type silsesquioxane.
[0039] Preferably, the preparation method of the organic-inorganic hybrid material cage-type silsesquioxane comprises the following steps:
[0040] Step 1: Mix 8-12 ml of vinyl triethoxysilane, 70-80 ml of acetone, 10-15 ml of hydrochloric acid and 12-18 ml of deionized water, and react at 30-50° C. for 10-20 hours to obtain an incompletely condensed polysilsesquioxane;
[0041] Step 2, ultrasonically disperse antimony trioxide and aluminum hydroxide, then dropwise add vinyl triethoxysilane while stirring, the addition amount of vinyl triethoxysilane is 10-20% of the total mass, then transfer vinyl triethoxysilane-antimony trioxide-aluminum hydroxide to incomplete condensation polysilsesquioxane, continue to react at a temperature of 30-50° C. for 2-6 hours, and finally filter and wash to obtain antimony trioxide-aluminum hydroxide composite POSS material;
[0042] Step three, add 18-22g antimony trioxide-aluminum hydroxide composite POSS material, 60-69g9,10-dihydro-9-oxa-10-phosphinothreant-10-oxa and 0.8-1.5g azobisisobutyronitrile to 75-120ml of toluene, react at 70-90°C for 10-20h under a nitrogen atmosphere, then cool and remove the upper liquid, dissolve the precipitate with 90-120ml of dichloromethane, and then add to 900-1200ml of ethyl acetate for rapid stirring, and finally filter and dry to obtain an organic-inorganic hybrid material cage-type silsesquioxane.
[0043] Although when antimony trioxide and aluminum hydroxide are used in combination, antimony trioxide and aluminum hydroxide will synergistically flame retard in different aspects, thereby obtaining a better flame retardant effect, the dispersibility of antimony trioxide and aluminum hydroxide is extremely poor. Even with the combination of a surface active coupled flame retardant additive, its dispersion performance is still insufficient.
[0044] In the present application, antimony trioxide and aluminum hydroxide are first modified with vinyltriethoxysilane, and then hydrolyzed with vinyltriethoxysilane to obtain antimony trioxide-aluminum hydroxide composite POSS material, thereby further improving the dispersibility of antimony trioxide and aluminum hydroxide, and ultimately achieving better mechanical properties for the rubber flame retardant material for flame retardant conveyor belts used in underground coal mines.
[0045] In addition, the antimony trioxide-aluminum hydroxide composite POSS material reacts with 9,10-dihydro-9-oxa-10-phosphophananthrene-10-oxa, thereby promoting the prepared organic-inorganic hybrid material cage-type silsesquioxane to simultaneously contain phosphophananthrene, silicon element, antimony trioxide and aluminum hydroxide, thereby further improving the flame retardant properties of rubber flame retardant materials for flame retardant conveyor belts used in underground coal mines.
[0046] Preferably, the reinforcing agent is carbon black, model N220.
[0047] Preferably, the active agent is one or both of zinc oxide and magnesium oxide.
[0048] Preferably, the antioxidant is one or two of antioxidant 4010 (N-cyclohexyl-N'-phenyl-p-phenylenediamine), antioxidant RD (2,2,4-trimethyl-1,2-dihydroquinoline polymer) and antioxidant 4020 (N-(1,3-dimethyl)butyl-N'-phenyl-p-phenylenediamine).
[0049] Preferably, the accelerator is one or both of CZ (N-cyclohexyl-2-benzothiazole sulfenamide) and DM (2,2'-dibenzothiazole disulfide).
[0050] Preferably, the vulcanizing agent is sulfur.
[0051] The method for preparing the flame retardant rubber material for the flame retardant conveyor belt used in underground coal mines comprises the following steps:
[0052] A. Mix the activator, antimony trioxide, aluminum hydroxide and a surface active coupled flame retardant additive, stir evenly, and dry at 40-60° C. to obtain component A;
[0053] B. Put natural rubber and butadiene rubber into an internal mixer, with the rotor speed at 30-35 r / min and the bolt pressure at 2.5-4.0 bar, and mix for 20-30 seconds to obtain component B;
[0054] C. Add component A, chlorinated paraffin, stearic acid, aromatic oil, antioxidant and accelerator to component B, and mix for 60-90 seconds to obtain component C;
[0055] D. Add 40-50% reinforcing agent to component C, mix for 100-120s, control the debonding temperature ≤130℃, debond; further mix on the open mixer (cut off twice, turn over three times), then roll down the sheet, pass through the release agent tank, and enter the wind room to cool to room temperature to obtain component D;
[0056] E. After the D component is left for 6-8 hours, it is put into an internal mixer, and a vulcanizing agent is added. The rotor speed is 20-25r / min, the top bolt pressure is 2.5-4.0bar, and the mixing is performed for 90-120s. The discharge temperature is controlled to be ≤95℃, and the rubber is discharged. After further mixing in the open mixer, the sheet is calendered, and after passing through the isolation agent tank, it enters the wind room to be cooled to room temperature to obtain the rubber flame retardant material for underground conveyor belts in coal mines.
[0057] In summary, this application has the following beneficial effects:
[0058] 1. The surface active coupled flame retardant additive in this application can promote the compatibility between rubber polymer materials and reinforcing agents, activators, antioxidants, accelerators, flame retardant fillers and vulcanizers, promote the mutual dispersion, mixing and coupling between different components, thereby improving the production process and improving the physical and mechanical properties of the material; catalyze and promote the carbonization of the material during combustion, thereby improving the flame retardant properties of the material.
[0059] 2. The surface active coupled flame retardant additive in the present application integrates the surfactant group and the silane coupling agent group into the same molecule, so that the surface active coupled flame retardant additive has the chemical properties of both the surfactant and the silane coupling agent, forming a new structure of the surface active coupled flame retardant additive molecule.
[0060] 3. The surface active coupled flame retardant additive in this application mainly has three functions: (a) It contains siloxane groups and hydroxyl groups, and plays the role of silane coupling agent. (b) It contains hydrophobic alkyl, sodium sulfonate group, carboxyl group and quaternary ammonium salt group, and plays the role of surfactant, dispersant and surface modifier. (c) It contains sodium sulfonate group, which plays the role of catalyst, promotes the catalytic carbonization of the material when it is thermally decomposed, and improves the thermal stability and flame retardant performance of the material; and it contains flame retardant element silicon in the molecule, which has flame retardant effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] Figure 1 This is the infrared spectrum analysis diagram of the surface active coupled flame retardant additive in Example 1. DETAILED DESCRIPTION
[0062] The following is combined with Figure 1 , Examples 1-6 and Comparative Examples 1-2 further illustrate the present application in detail.
[0063] raw material:
[0064] Octadecanamine CAS: 124-30-1; 3-glycidyloxypropyltrimethoxysilane CAS: 2530-83-8; isopropanol CAS: 67-63-0; acrylic acid CAS: 79-10-7; sodium 3-chloro-2-hydroxypropylsulfonate CAS: 126-83-0; natural rubber standard No. 1; butadiene rubber BR9000; reinforcing agent carbon black N220; activator zinc oxide CAS: 1314-13-2; stearic acid; aromatic oil; antioxidant RD 2,2,4-trimethyl-1,2-dihydroquinoline polymer; antioxidant 4010 N-cyclohexyl-N'-phenyl-p-phenylenediamine; accelerator CZ N-cyclohexyl-2-benzothiazole sulfenamide; accelerator DM 2,2'-Dibenzothiazole disulfide; Chlorinated paraffin 70; Antimony trioxide CAS: 1309-64-4; Aluminum hydroxide ATH-8; Curing agent - sulfur CAS: 7704-34-9; Vinyl triethoxysilane CAS: 78-08-0; 9,10-Dihydro-9-oxa-10-phosphophananthrene-10-oxa CAS: 35948-25-5; Azobisisobutyronitrile CAS: 78-67-1; Dichloromethane CAS: 75-09-2; Ethyl acetate CAS: 141-78-6.
[0065] Example
[0066] Example 1
[0067] A rubber flame retardant material for an underground conveyor belt in a coal mine, comprising the following raw materials: 50kg natural rubber, 50kg butadiene rubber, 45kg carbon black N220, 5kg zinc oxide, 2kg stearic acid, 5kg aromatic oil, 1.5kg antioxidant RD, 1.0kg antioxidant CZ, 1.3kg accelerator CZ, 0.5g accelerator DM, 25kg chlorinated paraffin 70, 4kg antimony trioxide, 15kg aluminum hydroxide ATH-, 0.3kg a surface active coupled flame retardant additive and 2kg vulcanizing agent-sulfur.
[0068] The preparation method of the rubber flame retardant material for underground conveyor belts in coal mines comprises the following steps:
[0069] A. Mix 15 kg of aluminum hydroxide and 0.3 kg of a surface active coupled flame retardant additive, stir evenly, and dry at 50° C. to obtain component A;
[0070] B. Put 50kg of natural rubber and 50kg of butadiene rubber into an internal mixer, with a rotor speed of 33r / min and a top bolt pressure of 3.5bar, and mix for 25s to obtain component B;
[0071] C. Add component A, 25kg chlorinated paraffin 70, 5kg zinc oxide, 4kg antimony trioxide, 2kg stearic acid, 5kg aromatic oil, 1.5kg antioxidant RD, 1.0kg antioxidant CZ, 1.3kg accelerator CZ and 0.5g accelerator DM to component B, and continue mixing for 80s to obtain component C;
[0072] D. Add 45kg of reinforcing agent carbon black N220 to component C, continue mixing for 110s, control the debonding temperature ≤130℃, debond; further mix on the open mill (cut off twice, turn over three times), then calender the sheet, pass through the release agent tank, and enter the wind room to cool to room temperature to obtain component D;
[0073] E. After the D component is left for 8 hours, it is put into an internal mixer, 2 kg of sulfur vulcanizer is added, the rotor speed is 22 r / min, the top bolt pressure is 3.5 bar, and the mixing is performed for 110 seconds. The discharge temperature is controlled to be ≤95°C, and the rubber is discharged; after further mixing in the open mixer, the sheet is calendered, and after passing through the isolation agent tank, it enters the wind room to be cooled to room temperature, and the rubber flame retardant material for underground conveyor belts in coal mines is obtained.
[0074] Among them, the molecular structure of the additive with surface active coupled flame retardant effect is: .
[0075] The preparation method of the surface active coupled flame retardant additive comprises the following steps:
[0076] S1. Dissolve 269.51 g of octadecylamine in 650 g of isopropanol, add 245.8 g of 3-glycidyloxypropyltrimethoxysilane, and react at 75° C. with stirring for 4 h to obtain intermediate M; the structural formula of intermediate M is: ;
[0077] S2. Add 75.0 g of acrylic acid to the intermediate M, stir and react at 75° C. for 3 h to obtain the intermediate N; the structural formula of the intermediate N is: ;
[0078] S3. Add 440 g of water to 220.6 g of sodium 3-chloro-2-hydroxypropyl sulfonate (content 98%) to dissolve and obtain an aqueous solution of sodium 3-chloro-2-hydroxypropyl sulfonate; add the aqueous solution of sodium 3-chloro-2-hydroxypropyl sulfonate to the intermediate N, stir and react at 75° C. for 5 h to obtain a surface active coupled flame retardant additive.
[0079] The reaction equations of each step of the preparation method of the surface-active silane coupling agent are:
[0080] S1: ;
[0081] S2: ;
[0082] S3: .
[0083] Infrared spectroscopy analysis of surface active silane coupling agents such as Figure 1 shown.
[0084] Depend on Figure 1 It can be seen that:
[0085] 3361 cm-1 (peak 1) is the OH stretching vibration peak;
[0086] 2918 cm-1 (peak 2) is the asymmetric stretching vibration peak of CH2;
[0087] 2850 cm-1 (peak 3) is the symmetric stretching vibration peak of CH2;
[0088] 1714 cm-1 (peak 4) is the stretching vibration peak of carboxylic acid C=O;
[0089] 1467 cm-1 (peak 5) is the asymmetric bending vibration peak of CH2;
[0090] 1379 cm-1 (peak 6) is the symmetrical bending vibration peak of CH2;
[0091] 1197 cm-1 (peak 7) is the symmetric stretching vibration peak of sulfonic acid group S=O;
[0092] 1041 cm-1 (peak 8) is the asymmetric stretching vibration peak of sulfonic acid group S=O;
[0093] 817 cm-1 (peak 9) is the Si-C stretching vibration peak;
[0094] 721 cm-1 (peak 10) is the CH2 in-plane rocking vibration peak;
[0095] 482 cm-1 (peak 11) is the Si-O peak.
[0096] Example 2
[0097] The difference from Example 1 is that the amount of the surface-active silane coupling agent added was adjusted from 0.3 kg to 0.75 kg.
[0098] Example 3
[0099] The difference from Example 1 is that the added amount of the surface-active silane coupling agent is adjusted from 0.3 kg to 1.5 kg.
[0100] Example 4
[0101] The difference from Example 1 is that the components and preparation method of the rubber flame retardant material for underground conveyor belts in coal mines are slightly different, as follows.
[0102] A rubber flame retardant material for an underground conveyor belt in a coal mine, comprising the following raw materials: 50kg natural rubber, 50kg butadiene rubber, 45kg carbon black N220, 5kg zinc oxide, 0kg stearic acid, 5kg aromatic oil, 1.5kg antioxidant RD, 1.0kg antioxidant CZ, 1.3kg accelerator CZ, 0.5g accelerator DM, 25kg chlorinated paraffin 70, 4kg antimony trioxide and 15kg aluminum hydroxide ATH-8, 0.24kg surface-active silane coupling agent and 2kg vulcanizing agent-sulfur.
[0103] The preparation method of the rubber flame retardant material for underground conveyor belts in coal mines comprises the following steps:
[0104] Step 1: 5 kg of zinc oxide, 4 kg of antimony trioxide, 15 kg of aluminum hydroxide and 0.24 kg of a surface-active silane coupling agent are mixed, stirred evenly, and dried at a temperature of 50° C. to obtain component A;
[0105] Step 2: 50 kg of natural rubber and 50 kg of butadiene rubber are put into an internal mixer at a rotor speed of 33 r / min and a top bolt pressure of 3.5 bar, and mixed for 25 seconds to obtain component B;
[0106] Step 3: Add component A, 25kg chlorinated paraffin 70, 0kg stearic acid, 5kg aromatic oil, 1.5kg antioxidant RD, 1.0kg antioxidant CZ, 1.3kg accelerator CZ and 0.5g accelerator DM to component B, and continue mixing for 80s to obtain component C;
[0107] Step 4: Add 45kg of reinforcing agent carbon black N220 to component C, continue mixing for 110s, control the debonding temperature to ≤130°C, debond; further mix on an open mixer (cut off twice, turn over three times), then roll down the sheet, pass through a release agent tank, and enter a wind room to cool to room temperature to obtain component D;
[0108] Step 5: After the D component is parked for 8 hours, it is put into an internal mixer, 2 kg of sulfur vulcanizer is added, the rotor speed is 22 r / min, the top bolt pressure is 3.5 bar, and the mixing is performed for 110 seconds. The discharge temperature is controlled to be ≤95°C, and the rubber is discharged; after further mixing in the open mixer, the lower sheet is calendered, and after passing through the isolation agent tank, it enters the wind room to cool to room temperature, and a rubber flame retardant material for underground conveyor belts in coal mines is obtained.
[0109] Example 5
[0110] The difference from Example 4 is that the added amount of the surface-active silane coupling agent is adjusted from 0.24 kg to 0.72 kg.
[0111] Example 6
[0112] The difference from Example 4 is that in step 1, antimony trioxide and aluminum hydroxide are doped into the organic-inorganic hybrid material cage-type silsesquioxane;
[0113] The preparation method of organic-inorganic hybrid material cage-type silsesquioxane comprises the following steps:
[0114] Step 1: Mix 10 ml of vinyl triethoxysilane, 75 ml of acetone, 10-15 ml of hydrochloric acid and 16 ml of deionized water, and react at 40° C. for 16 hours to obtain an incompletely condensed polysilsesquioxane;
[0115] Step 2: ultrasonically disperse antimony trioxide and aluminum hydroxide, then dropwise add vinyl triethoxysilane while stirring, the addition amount of vinyl triethoxysilane is 12% of the total mass, then transfer vinyl triethoxysilane-antimony trioxide-aluminum hydroxide to incomplete condensation polysilsesquioxane, continue to react at a temperature of 40° C. for 4 hours, and finally filter and wash to obtain antimony trioxide-aluminum hydroxide composite POSS material;
[0116] Step three, add 21g antimony trioxide-aluminum hydroxide composite POSS material, 66g9,10-dihydro-9-oxa-10-phosphinothreant-10-oxa and 1.2g azobisisobutyronitrile to 100ml of toluene, react at 80°C for 16h under a nitrogen atmosphere, then cool and remove the upper liquid, dissolve the precipitate with 100ml of dichloromethane, and then add to 1000ml of ethyl acetate for rapid stirring, and finally filter and dry to obtain an organic-inorganic hybrid material cage-type silsesquioxane.
[0117] Comparative Example
[0118] Comparative Example 1
[0119] The difference from Example 1 is that no surface-active silane coupling agent is added.
[0120] Comparative Example 2
[0121] The difference from Example 4 is that no surface-active silane coupling agent is added.
[0122] Performance testing
[0123] Detection Methods
[0124] Three samples were taken from Examples 1-6 and Comparative Examples 1-2 respectively, and then the various properties of the samples were tested with reference to MT / T914-2019 "Fabric Core Flame-Retardant Conveyor Belts for Coal Mines" and GB / T10707-2008 "Determination of Rubber Combustion Performance", and the average values were taken.
[0125] The test data are shown in Tables 1 and 2.
[0126] Table 1 Performance test table of Examples 1-3 and Comparative Example 1
[0127]
[0128] Referring to Examples 1-3 and Comparative Example 1 and in combination with Table 1, it can be seen that, relative to Comparative Example 1, the tensile strength and elongation of Example 1 are significantly improved, while the oxygen index of Example 1 does not change much, which indicates that the addition of a surface active silane coupling agent can significantly improve the mechanical properties of the conveyor belt rubber material without affecting its flame retardant properties.
[0129] The reason is that the surface active coupled flame retardant additive in the present application mainly plays three functions: (a) contains siloxane groups and hydroxyl groups, which play the role of silane coupling agent. (b) contains hydrophobic alkyl, sodium sulfonate group, carboxyl group and quaternary ammonium salt group, which plays the role of surfactant, dispersant and surface modifier, thereby improving the negative effects caused by poor dispersibility of powder flame retardant filler. (c) contains sodium sulfonate group, which plays the role of catalyst, promotes the catalytic carbonization of the material when it is thermally decomposed, and improves the thermal stability and flame retardant performance of the material; and contains flame retardant element silicon in the molecule, which has flame retardant effect.
[0130] Compared with Example 1, the tensile strength and oxygen index of Example 2 are slightly improved, and the elongation and hardness of Example 2 are slightly decreased. Compared with Example 2, the tensile strength, elongation and oxygen index of Example 3 are obviously decreased, which shows that although the addition of a large amount of surfactant coupled flame retardant additives can make the conveyor belt rubber material obtain extremely good mechanical properties and flame retardant properties, excessive addition of surfactant coupled flame retardant additives will reduce the mechanical properties and flame retardant properties of the conveyor belt rubber material.
[0131] Table 2 Performance test table of Examples 4-6 and Comparative Example 2
[0132]
[0133] With reference to Comparative Example 2 and Examples 4-5 and in combination with Table 2, it can be seen that, relative to Comparative Example 2, the tensile strength and elongation of Examples 4-5 are significantly improved, and the mean and maximum values of the alcohol burner flame combustion test of Examples 4-5 are significantly reduced, which indicates that the addition of a surface active coupled flame retardant additive can enable the conveyor belt rubber material to obtain extremely excellent mechanical properties and flame retardant properties.
[0134] The reason is that the surface active coupled flame retardant additive also acts as a catalyst, thereby promoting the flame retardant properties of the conveyor belt rubber material to catalyze carbonization, thereby improving the thermal stability and flame retardant properties of the material; and the presence of elemental silicon provides excellent flame retardant properties.
[0135] With reference to Example 4 and Example 6 and in combination with Table 2, it can be seen that, relative to Example 4, the tensile strength and elongation of Example 6 are significantly improved, and the mean and maximum values of the alcohol burner flame combustion test of Example 6 are significantly reduced, which indicates that when antimony trioxide and aluminum hydroxide are doped in the organic-inorganic hybrid material cage-type silsesquioxane, the flame retardant properties of the conveyor belt rubber material will have better flame retardant properties and mechanical properties.
[0136] The reason is that, although when antimony trioxide and aluminum hydroxide are used in combination, antimony trioxide and aluminum hydroxide will synergistically flame retard in different aspects, thereby obtaining a better flame retardant effect, the dispersibility of antimony trioxide and aluminum hydroxide is extremely poor. Even with the addition of a surface active coupled flame retardant additive, their dispersion performance is still insufficient.
[0137] In the present application, antimony trioxide and aluminum hydroxide are first modified with vinyltriethoxysilane, and then hydrolyzed with vinyltriethoxysilane to obtain antimony trioxide-aluminum hydroxide composite POSS material, thereby further improving the dispersibility of antimony trioxide and aluminum hydroxide, and ultimately achieving better mechanical properties for the rubber flame retardant material for flame retardant conveyor belts used in underground coal mines.
[0138] In addition, the antimony trioxide-aluminum hydroxide composite POSS material reacts with 9,10-dihydro-9-oxa-10-phosphophananthrene-10-oxa, thereby promoting the prepared organic-inorganic hybrid material cage-type silsesquioxane to simultaneously contain phosphophananthrene, silicon element, antimony trioxide and aluminum hydroxide, thereby further improving the flame retardant properties of rubber flame retardant materials for flame retardant conveyor belts used in underground coal mines.
[0139] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A surface active coupled flame retardant additive, characterized in that: Its molecular structure is: 。 2. A method for preparing the surface active coupled flame retardant additive according to claim 1, characterized in that: The following steps are involved: S1. Add octadecylamine and isopropanol into a reactor, and then add 3-glycidyloxypropyltrimethoxysilane, and mix and react to obtain an intermediate M. The structural formula of the intermediate M is: ; S2. Add acrylic acid to the intermediate M, mix and react to obtain the intermediate N, the structural formula of the intermediate N is: ; S3. Adding an aqueous solution of sodium 3-chloro-2-hydroxypropyl sulfonate to the intermediate N, mixing and reacting, to obtain a surface active coupled flame retardant additive.
3. The method for preparing the surface active coupled flame retardant additive according to claim 2, characterized in that: The molar ratio of octadecylamine, 3-glycidyloxypropyltrimethoxysilane, acrylic acid and sodium 3-chloro-2-hydroxypropylsulfonate is 1:(1.0-1.2):(1.0-1.2):(1.0-1.3); and / or; The mass ratio of octadecylamine to isopropanol is 1:(1.5-3.5).
4. The method for preparing the surface active coupled flame retardant additive according to claim 2, characterized in that: In S1, the reaction temperature is 65-80°C and the reaction time is 3-5h; and / or; In S2, the reaction temperature is 65-80°C and the reaction time is 2-4h; and / or; In S3, the reaction temperature is 65-80°C and the reaction time is 4-6h.
5. An application of the surface active coupled flame retardant additive according to claim 1, wherein the surface active coupled flame retardant additive is used for rubber flame retardant materials for flame retardant conveyor belts used in coal mines.
6. The use of the surface active coupled flame retardant additive according to claim 5, characterized in that: The flame retardant rubber material for flame retardant conveyor belts used in underground coal mines comprises the following raw materials in parts by weight: 40-60 parts of natural rubber, 40-60 parts of butadiene rubber, 40-50 parts of reinforcing agent, 4-6 parts of activator, 0-3 parts of stearic acid, 4-6 parts of aromatic oil, 1.5-3.5 parts of antioxidant, 0.8-2.8 parts of accelerator, 20-30 parts of chlorinated paraffin, 2-6 parts of antimony trioxide, 10-20 parts of aluminum hydroxide, 0.1-0.75 parts of surface active coupled flame retardant additive and 1-4 parts of vulcanizing agent.
7. The use of the surface active coupled flame retardant additive according to claim 6, characterized in that: The antimony trioxide and aluminum hydroxide are doped into the organic-inorganic hybrid material cage-type silsesquioxane.
8. The use of the surface active coupled flame retardant additive according to claim 7, characterized in that: The preparation method of the organic-inorganic hybrid material cage-type silsesquioxane comprises the following steps: Step 1: Mix 8-12 ml of vinyl triethoxysilane, 70-80 ml of acetone, 10-15 ml of hydrochloric acid and 12-18 ml of deionized water, and react at 30-50° C. for 10-20 hours to obtain an incompletely condensed polysilsesquioxane; Step 2, ultrasonically disperse antimony trioxide and aluminum hydroxide, then dropwise add vinyl triethoxysilane while stirring, the addition amount of vinyl triethoxysilane is 10-20% of the total mass, then transfer vinyl triethoxysilane-antimony trioxide-aluminum hydroxide to incomplete condensation polysilsesquioxane, continue to react at a temperature of 30-50° C. for 2-6 hours, and finally filter and wash to obtain antimony trioxide-aluminum hydroxide composite POSS material; Step three, add 18-22g antimony trioxide-aluminum hydroxide composite POSS material, 60-69g9,10-dihydro-9-oxa-10-phosphinothreant-10-oxa and 0.8-1.5g azobisisobutyronitrile to 75-120ml of toluene, react at 70-90°C for 10-20h under a nitrogen atmosphere, then cool and remove the upper liquid, dissolve the precipitate with 90-120ml of dichloromethane, and then add to 900-1200ml of ethyl acetate for rapid stirring, and finally filter and dry to obtain an organic-inorganic hybrid material cage-type silsesquioxane.
9. The use of the surface active coupled flame retardant additive according to claim 6, characterized in that: The reinforcing agent is carbon black, model N220; and / or; The active agent is one or both of zinc oxide and magnesium oxide; and / or; The accelerator is one or two of CZ and DM; and / or; The vulcanizing agent is sulfur; The antioxidant is one or two of antioxidant 4010, antioxidant RD and antioxidant 4020.
10. The use of the surface active coupled flame retardant additive according to claim 6, characterized in that: The method for preparing the flame retardant rubber material for the flame retardant conveyor belt used in underground coal mines comprises the following steps: A. Mix the activator, antimony trioxide, aluminum hydroxide and a surface active coupled flame retardant additive, stir evenly, and dry at 40-60° C. to obtain component A; B. Put natural rubber and butadiene rubber into an internal mixer, with the rotor speed at 30-35 r / min and the top bolt pressure at 2.5-4.0 bar, and mix for 20-30 seconds to obtain component B; C. Add component A, chlorinated paraffin, stearic acid, aromatic oil, antioxidant and accelerator to component B, and mix for 60-90 seconds to obtain component C; D. Add 40-50% reinforcing agent to component C, mix for 100-120s, control the debonding temperature ≤130℃, debond; further mix on the open mixer and roll down the sheet, pass through the isolation agent tank and enter the air room to cool to room temperature to obtain component D; E. After the D component is left for 6-8 hours, it is put into an internal mixer, and a vulcanizing agent is added. The rotor speed is 20-25r / min, the top bolt pressure is 2.5-4.0bar, and the mixing is performed for 90-120s. The discharge temperature is controlled to be ≤95℃, and the rubber is discharged. After further mixing in the open mixer, the sheet is calendered, and after passing through the isolation agent tank, it enters the wind room to be cooled to room temperature to obtain the rubber flame retardant material for underground conveyor belts in coal mines.
Citation Information
Patent Citations
Compounds comprising modified diorganosiloxane polymers
CN107001858A
Antimony-free high-wear-resistance flame-retardant conveying belt and preparation method thereof
CN117183500A